Roles of the basis functions on the weight function generating subspace construction - (:unkn) unknown (My University, 2010)
The purpose of this work is experimentation to understand the role of the basis functions in the weight function construction for one node integration. All theoretical background is taken from a recent work of our group. We present no results here. Only a limited portion of the numerical implementation results will be reported during the presentation in the conference. © 2010 American Institute of Physics.
Keywords: Fluctuationlessness Theorem; Hilbert Spaces; Matrix Representation; Numerical Integration; One Node Fluctuation Free Integration; Quadrature; Weight Functions